THE IMPORTANCE OF COOPERATIVE PEDAGOGY IN IMPROVING THE EFFICIENCY OF THE EDUCATIONAL PROCESS - Radjabova Inobat Ravshanovna (Web of Journals Publishing, 2023)
This article examines the unique aspects and importance of cooperation in the educational process, that is, the use of the strategy of students' work with each other or with a group.
Keywords: cooperation technique, group work, pair work, cooperative education, constructivism.